Life history traits of spotted lanternfly (Hemiptera: Fulgoridae) when feeding on grapevines and tree of heaven - Laveaga, Erica; Hoover, Kelli; Acevedo, Flor E. (Frontiers in Insect Science, 2023)
The invasive planthopper, spotted lanternfly (SLF), Lycorma delicatula (White) (Hemiptera: Fulgoridae), feeds on a broad range of plants including species of economic importance such as grape. Although SLF feeds on wild and cultivated grape, the effect of grapevines on the insect’s life history traits is unknown. This study examined the effect of cultivated Concord grapevines (Vitis labrusca) and the insect’s preferred host tree of heaven (TOH), Ailanthus altissima, on SLF development, survival, reproduction, and body mass. Newly emerged nymphs were allowed to feed on either TOH, Concord grapevines or a mixed diet of Concord grapevines plus TOH through adulthood until death. Development, mortality, and oviposition of paired adults were tracked daily to calculate the SLF rate of development, survival, and reproduction among treatments. When feeding exclusively on Concord grapevines, SLF was able to develop and reproduce but had higher mortality, slower development, and produced fewer eggs. SLF fed on the mixed diet of grapevines plus TOH exhibited faster nymphal development, laid more eggs, and had higher body mass compared with those fed only on grape or TOH. SLF had greater survival when fed on either the mixed diet or on TOH alone. We conclude that Concord grapevines are a poor-quality host for SLF, but when combined with TOH, SLF fitness increases above that of feeding on TOH alone. This study supports the elimination of TOH as a part of SLF vineyard management practices.